Construction and analysis of a lncRNA–miRNA–mRNA competing endogenous RNA network from inflamed and normal synovial tissues after anterior cruciate ligament and/or meniscus injuries - Xiao, Xiling; Yang, Xiaofan; Ren, Sen; Meng, Chunqing; Yang, Zhaohui (Frontiers in Genetics, 2022)
Background: Despite ample evidence demonstrating that anterior cruciate ligament (ACL) and meniscus tears are associated with the development of knee osteoarthritis (OA), the contributing factors remain unknown. Synovial inflammation has recently been recognized as a pivotal factor in the pathogenesis of OA. However, there is a lack of data on synovial profiles after ACL or meniscus injuries, which may contribute to posttraumatic OA (PTOA). Methods: Twelve patients with ACL tears and/or meniscus injuries undergoing surgery were recruited. During surgery, synovial tissues were obtained from the injured knees. The inflammation status of the synovium was characterized according to macroscopic criteria, and the synovium was classified as normal (control group) or inflamed (inflamed group). The histological characteristics of the biopsy samples were confirmed according to hematoxylin and eosin staining. We conducted high-throughput RNA sequencing on these synovial samples (3 vs. 3) to identify the differentially expressed (DE) RNAs. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, and protein–protein interaction (PPI) analyses were performed to investigate mRNAs with significant differences between the inflamed and normal/reactive groups. Next, competing endogenous RNA (ceRNA) networks were constructed based on bioinformatics analyses and quantitative real-time polymerase chain reaction (RT–PCR) results. Results: The inflammatory features of the synovial samples assessed at arthroscopy were consistent with the histological synovitis grades. The results showed that 2793 mRNAs, 3392 lncRNAs and 211 miRNAs were significantly DE in inflamed synovial membranes compared with normal synovial membranes. GO and KEGG analyses revealed that DE mRNAs were significantly enriched in immune and inflammatory processes and were highly correlated with the pathogenesis of PTOA. PPI networks demonstrated critical DE mRNAs between the two groups. Seven mRNAs, 4 lncRNAs and 4 miRNAs were validated by RT–PCR and were consistent with the RNA-seq data. Furthermore, lncRNA–miRNA–mRNA ceRNA regulatory networks were constructed based on bioinformatics analyses and validated RNAs. Conclusions: Our study provides foundational synovium profiles and shows that analyzing DE RNAs and ceRNA networks may provide new insights into the underlying mechanisms of PTOA. Future investigation of noncoding RNAs may also provide novel targets for treatment.